Influences in cartesian moral philosophy: general concepts - Solano Villarreal, Diana (2015)
In this first article, we explore the influences on the Cartesian moral philosophy which mainly refer to antiquity. Aristotle, Epicurus and the Stoics are the most in-depth sources. Moreover, the general concepts we consider most important to further develop the central thesis of this work (the role of moral philosophy Cartesian forms of domination towards the human being in modernity), are reviewed in this section. The concepts of virtue, habit, will, generosity, bliss, reason, wisdom, philosophy and the sovereign good, are analyzed. We also make a small reference to Scotus influence of the hand of genius Etienne Gilson. We search for clues that prove that the Cartesian morality can lead to a relationship of control of some human beings over others.